Computational Methods in Decision-Making, Economics and Finance - (:unkn) unknown (My University, 2002)
Computing has become essential for the modeling, analysis, and optimization of systems. This book is devoted to algorithms, computational analysis, and decision models. The chapters are organized in two parts: optimization models of decisions and models of pricing and equilibria.